2011
DOI: 10.1007/s12665-011-1145-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between land surface temperature and land use/land cover in Guangzhou, China

Abstract: The integration of remote sensing, geographic information system, landscape ecology and statistical analysis methods was applied to study the urban thermal environment in Guangzhou. Normalized Difference Vegetation Index (NDVI), Normalized Difference Build-up Index (NDBI), Normalized Difference Barren Index (NDBaI) and Modified Normalized Difference Water Index (MNDWI) were used to analyze the relationships between land surface temperature (LST) and land use/land cover (LULC) qualitatively. The result revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(82 citation statements)
references
References 27 publications
(29 reference statements)
4
77
0
1
Order By: Relevance
“…The result of this study is similar to the findings of Baguio City (mountain city) in the Philippines [7]. Additionally, the results of this study are comparable to tropical low land coastal cities like Jakarta (2.9 • C), Bangkok (2.2 • C) [11], and Guangzhou (2.8 • C) [44]. These changes in ∆ mean LST will intensify the impact of SUHI on the population of Kandy City.…”
Section: Suhi Intensity and Its Effectssupporting
confidence: 86%
“…The result of this study is similar to the findings of Baguio City (mountain city) in the Philippines [7]. Additionally, the results of this study are comparable to tropical low land coastal cities like Jakarta (2.9 • C), Bangkok (2.2 • C) [11], and Guangzhou (2.8 • C) [44]. These changes in ∆ mean LST will intensify the impact of SUHI on the population of Kandy City.…”
Section: Suhi Intensity and Its Effectssupporting
confidence: 86%
“…This could be due to the improvement in (2015) and Sun et al (2012) revealed that areas with rich vegetation cover have characterized by lowest LST. In Fig.…”
Section: Interpretation Of Lst and Savimentioning
confidence: 98%
“…Both NDVI and NDBI were considered as relating closely to UHI by Chen et al [2] who proposed two bivariate regression models between the NDVI, NDBI and the brightness temperature. Although Sun et al [58] revealed that the NDVI and NDBI were effective indicators for quantifying the impacts of LULC on the LST, it is necessary to further analyze the correlation among the LST, NDBI and NDVI to better understand the impacts of urban expansion and vegetation change on the urban thermal environment. As shown by Figure 10, higher LSTs are usually found in the areas of lower NDVI values and higher NDBI values because of the absence of vegetation cover or the predominance of high-density urban areas, including commercial, industrial, and some residential developments.…”
Section: Correlation Analysis Of Lst and Ndbi Ndvimentioning
confidence: 99%